2020
DOI: 10.9734/cjast/2020/v39i1630741
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Relevance of E-readiness Assessment Tools for ICT Use in Agriculture

Abstract: Information and Communication Technology is an indispensable part of modern society. As with everything else, it has a profound impact on various activities in the agriculture sector like research, cyber-extension, marketing and transfer of technologies leading to its sustainable development. The concept of E-readiness provides a unified framework to evaluate ICT infrastructure and the ability of its consumers, businesses, and governments to use ICT to their benefit. E-readiness is a state of preparedness to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This study has acknowledged the incredible work done by previous scholars have continued to propose and develop e-government frameworks (Malodia et al, 2021;Ahmad et al, 2021;Singh et al, 2020;Roblek et al, 2020;Dias, 2020), e-government readiness assessment tools (Alghamdi, Goodwin & Rampersad, 2016;Assefa et al, 2021;Kagoya & Gilbert, 2020;Haydari, 2020;Pal, Singh & Dhaliwal, 2020). And other studies have suggested models for egovernment implementation (Elbahnasawy, 2021;Li & Xue, 2021;Sharma et al, 2021;Li, 2021;Alkraiji, 2020).…”
Section: Introductionmentioning
confidence: 73%
“…This study has acknowledged the incredible work done by previous scholars have continued to propose and develop e-government frameworks (Malodia et al, 2021;Ahmad et al, 2021;Singh et al, 2020;Roblek et al, 2020;Dias, 2020), e-government readiness assessment tools (Alghamdi, Goodwin & Rampersad, 2016;Assefa et al, 2021;Kagoya & Gilbert, 2020;Haydari, 2020;Pal, Singh & Dhaliwal, 2020). And other studies have suggested models for egovernment implementation (Elbahnasawy, 2021;Li & Xue, 2021;Sharma et al, 2021;Li, 2021;Alkraiji, 2020).…”
Section: Introductionmentioning
confidence: 73%
“…Other factors perceived to offer greater advantage were greater top management support, greater organisational readiness and larger size. Equally important, several other studies also highlight the importance of technology (Hassen, Abd Rahim, & Shah, 2019;Yusif, Hafeez-Baig, & Soar, 2017;Pal, Singh, & Dhaliwal, 2020) in fostering e-commerce. As such, we hypothesise: H₂: Technological resources have an influence on e-commerce implementation.…”
Section: Technological Resources and E-commerce Implementationmentioning
confidence: 99%
“…MA is exemplified as external factors outside SMEs that covers opportunities and threats in Strength Weaknesses Opportunities and Threats (SWOT) analysis as well as demographic, economic, technology, environmental, political, government support, cultural, and broader competitor landscape (Kotler, 2000;Pal & Dhaliwal, 2020). For demographic, the deftness of digitalization is deliberated from personal internet users, particularly age, literacy rate, gender, income, culture, community, the population of locality, employment status, and domicile (Hanafizadeh et al, 2009;Pal & Dhaliwal, 2020). The government regulation that abutment the discharge of internet access and websites, the occasion of technical infrastructure also conferred in this schema (Vankudothu, 2014).…”
Section: Macro Environment (Ma)mentioning
confidence: 99%